HUBUNGAN KEBUTUHAN PERAWATAN ORTODONTI DENGAN MINAT PERAWATAN ORTODONTI CEKAT (Tinjauan Pada Pelajar SMA/Sederajat di Banjarmasin Kawasan Non-Perkotaan) - Arini Rusyda; Irnamanda D.H; Ika Kusuma Wardani; Melisa Budipramana; I Wayan Arya Krishnawan Firdaus (Universitas Lambung Mangkurat, 2026)
Background: Malocclusion is the misalignment of teeth that affects oral health and facial aesthetics. The prevalence of malocclusion in South Kalimantan is high, but the number of people undergoing orthodontic treatment is still low. The need for memengaruhi dalam menjalani perawatanc treatment is particularly high among adolescents, as malocclusion affects their psychosocial well-being and appearance. Many adolescents with malocclusion do not undergo treatment because they are unaware of the need for it. This indicates that, in addition to clinical need, interest also influences the decision to undergo treatment. Objective: This study aims to analyze the relationship between orthodontic treatment needs and interest in fixed orthodontic treatment among high school students in Banjarmasin, a non-urban area. Method: This study was an analytical observational study with a cross-sectional design. The sample consisted of 175 adolescents aged 15-18 years. A questionnaire on interest in fixed orthodontic treatment was used to measure interest in fixed orthodontic treatment. The Index of Complexity, Outcome, and Need (ICON) was used to assess the need for orthodontic treatment. Results: The Spearman test results showed a significance of 0.041 (p<0.05), indicating that there is a relationship between orthodontic treatment needs and interest in fixed orthodontic treatment. A correlation value of 0.155 indicates that there is a weak relationship between the need for orthodontic treatment and interest in fixed orthodontic treatment. Conclusion: There is a positive correlation between the need for orthodontic treatment and interest in fixed orthodontic treatment, with a weak coefficient. The greater the need for orthodontic treatment, the greater the interest in treatmentKeywords: High school students, ICON, Interest, Orthodontic treatment needs